The pharmacokinetics effects of the MCAO model on senkyunolide I in pseudo germ-free rats after oral co-administration of Chuanxiong and warfarin - Li, Haigang; Li, Fang; Zhou, Yi; Xiang, Zhongjun; Zhou, Bilan; Lan, Bin; Ruan, Xiaoling (Frontiers in Pharmacology, 2025)
AimTo investigate the pharmacokinetics effects of a middle cerebral artery occlusion (MCAO) model on senkyunolide I (SEI) in pseudo germ-free rats after oral co-administration of Chuanxiong and warfarin.MethodsRats were divided randomly into WC_H, WS_H, WC_HF, WS_HF, WC, WS, WC_F, and WS_F groups (W, warfarin; C, Chuanxiong; S, SEI; H, rats without an MCAO operation; F, pseudo germ-free). Pseudo germ-free rats were orally administered ciprofloxacin hydrochloride (50 mg/kg, twice a day) for 3 consecutive days, and the MCAO operation was carried out on the third day. Chuanxiong (10 g/kg) or SEI (7.5 mg/kg) and warfarin sodium (0.5 mg/kg) were orally administered only once on the fourth day. The plasma concentrations of SEI were determined by UPLC-MS/MS. Stool samples were collected for gut microbiota analyses. The coronal thin slices of the brain were dyed with triphenyl-2H-tetrazolium chloride.ResultsCompared to the WC_H group, the AUC0-t and Cmax of the WC group increased 2.08- and 1.79-fold (P < 0.001), respectively. Compared with the WS_H group, the AUC0-t and Cmax of the WS group decreased by 6.24% and 22.64% (P < 0.001), respectively. Compared to the WC_HF group, the AUC0-t and t1/2z of the WC_F group decreased by 60.95% and 35.26% (P < 0.01), respectively. Compared with the WS_HF group, the AUC0-t and Cmax of the WS_F group decreased by 2.87% and 8.54% (P < 0.001), respectively. Compared to the WC_H group, the AUC0-t and Cmax of the WC_HF group increased by 85.03% and 82.48% (P < 0.001), respectively. Compared with the WS_H group, the AUC0-t and Cmax of the WS_HF group increased 1.40-and 2.43-fold (P < 0.001), respectively. Compared to the WC group, the AUC0-t and t1/2z of the WC_F group decreased by 45.81% and 79.44% (P < 0.001), respectively. Compared with the WS group, the AUC0-t and t1/2z of the WS_F group decreased by 35.86% and 79.74% (P < 0.001), respectively.ConclusionBoth the MCAO operation and the pseudo germ-free condition significantly changed the pharmacokinetics characteristics of SEI after oral co-administration with warfarin and Chuanxiong or SEI. It is a promising way to understand the potential pharmacokinetics of herb–drug interactions from the angle of the gut microbiota.